Transforming livestock productivity through watershed interventions: A case study of Parasai-Sindh watershed in Bundelkhand region of Central India - Dev, I.; Singh, R.; Garg, K. K.; Ram, A.; Singh, D.; Kumar, N.; Dhyani, S. K.; Singh, A.; Anantha, K. H.; Akuraju, V.; Dixit, S.; Tewari, R.K.; et al. (Elsevier, 2022)
CONTEXT: Global experiences reveal the positive impact of watershed-based interventions in improving livelihoods and environmental security. In the drylands, increasing forage resources and improving livestock productivity is a critical challenge. OBJECTIVES: The overarching aim of this paper is to analyse the impact of watershed-based interventions on livestock population, productivity, fodder resources, and biomass availability. The paper describes the interrelationship between land, water, crop, and livestock and how the gap in forage deficit can be bridged through a range of watershed interventions. METHODS: The study was undertaken in the Parasai-Sindh watershed of Central India between 2011 and 2016. A 300-year-old defunct haveli (a traditional rainwater harvesting structure) was renovated and nine check dams along the drainage line were constructed. Nearly 25,000 running-meters of field bunds were constructed. Large fields (2-3 ha) were divided into relatively smaller plots (0.3–0.5 ha) to reduce runoff velocity. The impact of watershed interventions on water availability, livestock productivity, forage yield, and income was studied through hydrological monitoring, primary household survey and principal component analysis (PCA) biplot and hierarchical clustering. RESULTS AND CONCLUSIONS: The watershed interventions enhanced groundwater availability leading to greater fodder availability, 22% increase in livestock population (ACU) and a 120% increase in milk production over a period of five years. The bovine population recorded a surge of 193% (cattle) and 32% (buffalo) over this period. Mean dry matter (DM, fodder) availability also increased from 10 t/household/year to 16.7 t/household/year owing to improved water availability. Groundnut (rainy season) and wheat (post rainy season) contributed significantly as forage resources. There was an annual forage demand of 5560 t DM for a livestock population of 2175 ACU in 2011 and of 6770 t DM for a livestock population of 2650 ACU in 2016. Annual forage biomass availability was estimated at 4219 t DM in 2011 and 6977 t DM in 2016. There was a deficit of 1341 t DM (24%) in 2011 which turned into a 3% surplus of 210 t DM in 2016 through watershed-based interventions. With increased cropping intensity and milk production, average annual household income increased from US$ 1325 to US$ 2430 over the five-year period. SIGNIFICANCE: This case study clearly illustrates the impact of watershed-based interventions on livestock population, productivity, forage resources, and biomass availability to bridge the gap in forage deficit. Its findings serve as a guide to widely scale up watershed-based interventions for improved water and biomass availability, and livestock productivity in semi-arid and dryland regions.